2020
DOI: 10.21037/jtd-20-545
|View full text |Cite
|
Sign up to set email alerts
|

Sputum and serum autoantibody profiles and their clinical correlation patterns in COPD patients with and without eosinophilic airway inflammation

Abstract: Background: Autoimmunity plays a role in the pathogenesis of chronic obstructive pulmonary disease (COPD). However, the autoantibody responses and their clinical correlation patterns in COPD patients with and without airway eosinophilic inflammation are unknown. The aim of this study was to compare the autoantibody profiles and their clinical associations in stable COPD patients, stratified by airway inflammatory phenotypes.Methods: Matched sputum and serum, obtained from 62 stable COPD patients and 14 age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Future studies have to investigate the possibility of a cell-type specific effect of eHSPs as reported by others [ 41 ]. Furthermore, when assessing the effects of eHSP70 in the context of COPD the presence of inhibitory acting HSP auto-antibodies, which have been reported in COPD patient’s sputum and serum [ 42 ], has to be taken into account. Thus, it will be necessary to determine the ratio of free and antibody bound HSPs in COPD patient; such data are currently missing.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies have to investigate the possibility of a cell-type specific effect of eHSPs as reported by others [ 41 ]. Furthermore, when assessing the effects of eHSP70 in the context of COPD the presence of inhibitory acting HSP auto-antibodies, which have been reported in COPD patient’s sputum and serum [ 42 ], has to be taken into account. Thus, it will be necessary to determine the ratio of free and antibody bound HSPs in COPD patient; such data are currently missing.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective measurement of inflammatory markers following Ig administration, such as erythrocyte sedimentation rate and C-reactive protein or sputum autoantibodies, would be informative. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“… 38 Although it has not been clearly established, serum and sputum autoantibodies (antibodies against self-antigens) may correlate with a certain COPD phenotype such as those with recurrent AECOPD. 39 Immunoglobulin treatment has been used successfully to treat many immune-mediated diseases caused by autoreactive B lymphocytes. Immunoglobulin is found to exert its effect through modulation of expression and function of FcR, interference with complement activation and the cytokine network.…”
Section: Introductionmentioning
confidence: 99%